Revisiting perfectionism in high-level ballet: A longitudinal collective instrumental case study - Nordin-Bates, S. M.; Aldoson, M.; Downing, C. (The Sport Psychologist, 2023)
Using a case study design, we explored two ballet dancers` perfectionism experiences via interviews and questionnaires at two time points 5 years apart. They represented the two types of "pure perfectionism" in the 2 × 2 model of perfectionism: a female representing pure personal standards perfectionism (high perfectionistic strivings, low perfectionistic concerns) and a male representing pure evaluative concerns perfectionism (low perfectionistic strivings, high perfectionistic concerns). The pure personal standards perfectionism dancer reported stable perfectionism across time, seemingly resilient to any perfectionistic concerns developing. She attributed this to her stable, grounded personality, also reporting autonomous motivation and performance success. The dancer representing pure evaluative concerns perfectionism reported increased perfectionistic strivings and lowered perfectionistic concerns over time; concurrently, his motivation became less controlled and more autonomous. He described the reasons in terms of improved basic psychological needs satisfaction and personal growth. Overall, autonomy might be important in mitigating perfectionism.